Development of a Manual Book on Processing Flour of Mole Crab to Provide Students Science Process Skills - Widia Gusti; Aceng Ruyani; Urip Santoso; Bhakti Karyadi; Euis Nursaadah (UIN Fatmawati Sukarno Bengkulu, 2025)
This study is an experimental model a group pretest-posttest design. This study aims to: 1) Describe the feasibility of the manual book in learning to train students science process skills based on the results of flour processing through validity tests and trials, 2) Describe the results of improving students science process skills based on the manual book of flour processing made from mole crab. Validation of the manual book was carried out by experts to determine the feasibility of the content, language and design aspects, the results is Aiken-V score of 0.86 (valid). The implementation of the use of manual books in learning was carried out on students majoring in culinary arts and industry at SMKN 7 Bengkulu. Students’ science process skills (SPS) (Observation, Interpretation, Hypothesize, Design an Experiment, Implementing Concept and Using tools and Materials) were measure Based on the results of the pre-test and post-test, Students majoring in Industry has n-gain score 0.41 (moderate) while the students majoring in culinary has n-gain score 0.70 (moderate). The use of manual book in learning is suitable for use as a teaching material for students because it can stimulate and improve students’ science process skills.